Lavendria Laundy and Dry Cleaning / Shahisnawi Bin Sauluhin … [et. al.] - Sauluhin, Shahisnawi; Abdul Rahim, Muhammad Zharif Iqbal; Azman, Imran Adib; Kok, Nadiatul Izzah; Zaidel, Aidah (2019)
This report examines Lavendria Laundry & Dry Cleaning which is an industry that focus on value laden relationships with its clients by providing them with convenient, professional, eco-friendly, efficient, effective and hygienic laundry services, folding services and oriented dry cleaning with affordable range of prices for the benefit of customers. The business was initiated by a group of five students namely, Shahisnawi, Imran, Zhariff, Aidah and Izzah. We intend to specialize in the provision of laundry services, folding services and dry cleaning service. Their services will encompass all laundry care and cleaning value based activities, namely; dry cleaning, laundry care, drying, pressing and folding. This exciting business venture will be based in the heart of UiTM Samarahan Campus 2 at Pusat Pelajar Seri Kenyalang.